Answer:
y=x+5
Step-by-step explanation:
So first you need to plug everything into the point-slope formula which is
y-y1=m(x-x1)
m being the slope and y1 and x1 being the point (5,10)
So once you plug it in it should look like this: y-10=1(x-5)
Now you solve it
First you need to distribute 1 in 1(x-5) which is (x-5)
Now you have y-10=x-5
Then you add 10 to both sides which is y=x+5
Your answer is y=x+5
Answer:
The product ![\frac{b-5}{2b}\times\frac{b^2+3b}{b-5}=\frac{b+3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bb-5%7D%7B2b%7D%5Ctimes%5Cfrac%7Bb%5E2%2B3b%7D%7Bb-5%7D%3D%5Cfrac%7Bb%2B3%7D%7B2%7D)
Step-by-step explanation:
Given expression
and ![\frac{b^2+3b}{b-5}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%5E2%2B3b%7D%7Bb-5%7D)
We have to find the product of ![\frac{b-5}{2b}\times\frac{b^2+3b}{b-5}](https://tex.z-dn.net/?f=%5Cfrac%7Bb-5%7D%7B2b%7D%5Ctimes%5Cfrac%7Bb%5E2%2B3b%7D%7Bb-5%7D)
Consider the given expression ![\frac{b-5}{2b}\times\frac{b^2+3b}{b-5}](https://tex.z-dn.net/?f=%5Cfrac%7Bb-5%7D%7B2b%7D%5Ctimes%5Cfrac%7Bb%5E2%2B3b%7D%7Bb-5%7D)
Multiply fractions, we have,
![\frac{a}{b}\cdot \frac{c}{d}=\frac{a\:\cdot \:c}{b\:\cdot \:d}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7Bb%7D%5Ccdot%20%5Cfrac%7Bc%7D%7Bd%7D%3D%5Cfrac%7Ba%5C%3A%5Ccdot%20%5C%3Ac%7D%7Bb%5C%3A%5Ccdot%20%5C%3Ad%7D)
![=\frac{\left(b-5\right)\left(b^2+3b\right)}{2b\left(b-5\right)}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%5Cleft%28b-5%5Cright%29%5Cleft%28b%5E2%2B3b%5Cright%29%7D%7B2b%5Cleft%28b-5%5Cright%29%7D)
Cancel common factor ( b - 5 )
we have, ![=\frac{b^2+3b}{2b}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bb%5E2%2B3b%7D%7B2b%7D)
Apply exponent rule,
![\:a^{b+c}=a^ba^c](https://tex.z-dn.net/?f=%5C%3Aa%5E%7Bb%2Bc%7D%3Da%5Eba%5Ec)
![b^2=bb](https://tex.z-dn.net/?f=b%5E2%3Dbb)
![=bb+3b=b(b+3)](https://tex.z-dn.net/?f=%3Dbb%2B3b%3Db%28b%2B3%29)
![=\frac{b\left(b+3\right)}{2b}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bb%5Cleft%28b%2B3%5Cright%29%7D%7B2b%7D)
Cancel common factor b , we have,
![=\frac{b+3}{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bb%2B3%7D%7B2%7D)
Thus, the product ![\frac{b-5}{2b}\times\frac{b^2+3b}{b-5}=\frac{b+3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bb-5%7D%7B2b%7D%5Ctimes%5Cfrac%7Bb%5E2%2B3b%7D%7Bb-5%7D%3D%5Cfrac%7Bb%2B3%7D%7B2%7D)
Ik this is not what you were looking for but what kind of problem is this lol. i never seen this
This can be done easily if you choose a different probability.
Find the chance that none of the 5 graduates find a job.
For one student that is 100%-62%=38%
This has to happen for all 5 students, that is P=(0,38)^5=0,008 (rounded)
This is the chance that none of the 5 students finds a job. All of the above cases at least one finds a job.
That is 1-0,008=0,992 (rounded)